A statistical quality control study on Titan Rubber Industrial Manufacturing Corporation - Atienza, Maria Jazmin; Erpelo, Michael; Roman, Patricio Jr. (Department of Industrial Engineering and Operations Research College of Engineering, University of the Philippines Diliman, Quezon City, 1999)
Titan Rubber Industrial Manufacturing Corporation (TRIMC) is the sole producer of vehicle rubber products such as radiator hose and weatherstrips here in the Philippines. Just like any other production company TRIMC uses statistical quality control to improve their products and industrial processes. On the first semester of AY 1999-2000, a group of Industrial Engineering students from University of the Philippines, Diliman, decided to conduct a thorough study on the TRIMC quality control. Makers of this study focused on the TRIMC's weatherstrip since this is the bulk of their production (35 percent). The researchers provided sufficient documentation and analysis on the plant's industrial processes. Using the Failure Mode Effects and Analysis, the group proved that the mixing and splicing are the critical processes of the company. In the mixing process, variable control charting was used. 8-2 Charts were utilized to document and analyze the elongation, hardness and tensile strength of rubber. Apparently, the data gathered showed that the rubber material's elongation and tensile strength was out of control. Using Ishikawa analysis and Pareto diagram, it was proven that main cause of problem was the absence of division of labor. The researchers suggested having two or three personnel in the preparation of chemicals. TRIMC followed the said recommendation and anothe set of data was collected thereafter, resulting to a controlled process. The old and new data were compared using Process Capability Ratio (PCR). Old data produced a PCR of 1.02 and 1.50 while the new data had PCR of 2.70 and 1.56. Meaning the new process is more capable than the original. Attribute control charting was used in the splicing process. NP charts were utilized to determine the number and fraction of nonconformities in weathership production. The data that was accumulated showed that the fraction of nonconformities chart was out of control. Using basic statistical process control tools, it was known that causes of the variability were skill deficiency and malfunctioning machines. The researchers suggested providing hand gloves for the workers to avoid scratches of weatherships. Regular check-up of machines was also recommended. After making such adjustments, TRIMC gathered new data, which proved to be in control. In using suggested process, the company can save up to P7150.00 in repair costs. Finally, by using military standards 105E, the researchers suggested a sampling plan with the AOQL of 0.65 and inspection level 2, the normal sampling plan is (2,3) with lot size 1000.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: Titan Rubber Industrial Manufacturing Corporation; Statistics; Rubber industry and trade; Quality control